Strengthening the Internal Accountability Process in Police: Impediments and Way Forward - Riaz, Muhammad Fawad ud Din (Journal of Pakistan Administration, 2023)
The topic of this research article is “Strengthening the Internal Accountability Process in Police: Impediments and Way Forward”. The objective and purpose of this research is to identify the hurdles involved in internal accountability process of police in order to give recommendations for strengthening the said process. Extensive literature has been reviewed in order to identify gaps involved in the internal accountability process of police. Then, a comprehensive research methodology has been given for carrying out results, analysis and discussion. Lastly, conclusion and recommendations have been given for the police department to improve its internal accountability process.
Keywords: Internal Accountability Process; Internal Accountability Impediments; Pakistan Police Department